Understanding physics : student guide - Cassidy, David; Holton,Gerald; Rutherford, James (New York : Springer, 2002)
Understanding Physics is an innovative undergraduate course designed for students preparing to enter careers in fields outside of science or engineering, including students planning to teach, or already teaching, in K-12 classrooms. It is inspired by the famous Project Physics Course, which became known for placing the concepts of physics within the broader humanistic contexts in which they arose. The course materials comprise * The textbook, which is divided into two parts that may be studied in either order * This Student Guide, containing inquiry-based laboratory investigations and additional materials * An Instructor Guide with examination questions, resources, and other helpful information These components work together to provide an integrated educational experience in physics. The text contains questions designed to help students confirm what they have learned and to encourage them to explore further, by reading, by experimenting, and in group discussions. The inquiry-based laboratory investigations include in-depth explorations, student-designed inquiries, and text-related mini- laboratory explorations that may be used as hands-on activities or as demonstrations with student participation. The suggested equipment is deliberately "low tech" in order to afford students maximum experience with the phenomena. The apparatus is inexpensive and common to most instructional laboratories. Some ways to incorporate computer usage are suggested as students gain familiarity with the laboratory apparatus and methods
Keywords: Electronic books Laboratory manuals Llibres; Physique -- Manuels de laboratoire; electrònics Physics